Analisis Komponen Biaya Terhadap Pendapatan Bisnis Online Shop (Studi Kasus Pada Bisnis Online Shop Kota Surakarta) - Totok Susilo Pamuji Nugroho (JAMER : Jurnal Akuntansi Merdeka, 2021)
This study aims to determine the cost components needed to generate maximum income in the online shop business from January to June 2021. In order to generate maximum income, there are certainly many factors that must be considered. The population of this study is online business people in Surakarta, totaling 65 people, the sample selection criteria are online business people who earn below 100 million rupiah per year. Data collection techniques in this study are interviews and documentation. The results of this study indicate that the cost of expeditions, raw material costs and labor costs have a positive and significant impact on online shop business income in the city of Surakarta. Simultaneous test results also prove that expedition costs, raw material costs and labor costs also have a positive and significant effect on online shop business income in the city of Surakarta.